Performance analysis of multicarrier code division multiple access over rayleigh fading channel - Uddin, Jia; Faisal, Mohammed Fuad Ad; Azam, Md. Facihul; Muzahidur Rahman, A. F M (© 2012 Trans Tech Publications, 2016)
This conference paper was presented in the International Conference on Advanced Materials and Engineering Materials, ICAMEM2011; Shenyang, Liaoning; China; 22 November 2011 through 24 November 2011 [© 2012 Trans Tech Publications] The conference paper's definite version is available at: :http://dx.doi.org/10.4028/www.scientific.net/AMR.457-458.985